2017
DOI: 10.1007/s00429-017-1432-0
|View full text |Cite
|
Sign up to set email alerts
|

The neurons expressing calcium-binding proteins in the amygdala of the guinea pig: precisely designed interface for sex hormones

Abstract: The generation of emotional responses by the amygdala is determined largely by the balance of excitatory and inhibitory inputs to its principal neurons. These responses are often sex-specific, and any imbalance in excitatory and/or inhibitory tones leads to serious psychiatric disorders which occur with different rates in men versus women. To investigate the neural basis of sex-specific processing in the amygdala, relationships between the neurons expressing calbindin (CB), parvalbumin (PV) and calretinin (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 103 publications
(165 reference statements)
1
10
0
Order By: Relevance
“…A recent study in the AMY of the guinea pig reported that in various nuclei of the AMY, small subsets of CB neurons and substantial proportions of PV neurons co‐express ERβ, whereas many of the CR neurons co‐express ERα. Both of these estrogen‐sensitive populations are strictly separated, as CB and PV neurons almost never co‐express ERα, whereas CR cells are usually devoid of ERβ (Równiak ). By western blotting, we observed that ERα and ERβ both were decreased in the AMY of the OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the AMY of the guinea pig reported that in various nuclei of the AMY, small subsets of CB neurons and substantial proportions of PV neurons co‐express ERβ, whereas many of the CR neurons co‐express ERα. Both of these estrogen‐sensitive populations are strictly separated, as CB and PV neurons almost never co‐express ERα, whereas CR cells are usually devoid of ERβ (Równiak ). By western blotting, we observed that ERα and ERβ both were decreased in the AMY of the OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct distribution of CB and CR in the amygdaloid complex has been analyzed in diverse vertebrates and, specially in mammals, has served to subdivide these structures (Sorvari, Soininen, & Pitkanen, ,b; Kemppainen & Pitkanen, ; Ashwell, Hardman, & Paxinos, ; Legaz et al, ; Równiak, ). Nevertheless, there is a great variability in the specific content of CB and CR in each amygdaloid nucleus among species, which makes difficult the use of the distribution of calcium binding proteins as a criterion for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the exact physiological function of CB, CR, and PV is still not completely understood, they have been demonstrated to be important markers of separate neuronal populations in the adult brain (Arai et al ., ; Baimbridge et al ., ; Andressen et al ., ; Najdzion et al ., ; Równiak et al ., ; Wasilewska et al ., ; Hermanowicz‐Sobieraj et al ., ) and during brain ontogeny (Solbach and Celio, ; Zakowski and Robak, 2013; Hermanowicz‐Sobieraj and Robak, ). In the guinea pig, these proteins mark the vast majority of GABAergic neurons in amygdala, septum, and subicular complex (Równiak et al ., ; Wasilewska et al ., ; Hermanowicz‐Sobieraj and Robak, ; Równiak, ). In the amygdala neurons expressing CB and/or PV are sexually dimorphic and PV+ and CB+ neurons co‐express estrogen receptors beta (ERβ), while CR+ neurons co‐express estrogen receptors alpha (ERα) (Równiak et al ., ; Równiak, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the guinea pig, these proteins mark the vast majority of GABAergic neurons in amygdala, septum, and subicular complex (Równiak et al ., ; Wasilewska et al ., ; Hermanowicz‐Sobieraj and Robak, ; Równiak, ). In the amygdala neurons expressing CB and/or PV are sexually dimorphic and PV+ and CB+ neurons co‐express estrogen receptors beta (ERβ), while CR+ neurons co‐express estrogen receptors alpha (ERα) (Równiak et al ., ; Równiak, ). Both these estrogen‐sensitive populations are strictly separated as PV+ and CB+ neurons almost never co‐express ERα while CR+ cells are devoid of ERβ (Równiak, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation